Real‐world performance of hybrid closed loop in youth, young adults, adults and older adults with type 1 diabetes: Identifying a clinical target for hybrid closed‐loop use. Issue 9 (9th June 2021) - Berget, Cari; Akturk, Halis Kaan; Messer, Laurel H.; Vigers, Timothy; Pyle, Laura; Snell‐Bergeon, Janet; Driscoll, Kimberly A.; Forlenza, Gregory P.
Abstract: Aim: To describe real‐world hybrid closed loop (HCL) use and glycaemic outcomes across the lifespan and identify a clinical threshold for HCL use associated with meeting the internationally recommended target of 70% sensor glucose time in range (TIR; 70‐180 mg/dL). Materials and Methods: Mixed models examined MiniMed 670G HCL use and glycaemic outcomes in 276 people with type 1 diabetes from four age groups: youth (aged <18 years), young adults (18‐25 years), adults (26‐49 years) and older adults (≥50 years) for 1 year. ROC analysis identified the minimum percentage HCL use associated with meeting the TIR goal of 70%. Results: HCL use at month 1 was 70.7% ± 2.9% for youth, 71.0% ± 3.8% for young adults, 78.9% ± 2.1% for adults and 84.7% ± 3.8% in older adults. HCL use declined significantly at 12 months to 49.3% ± 3.2% in youth ( P  < .001) and 55.7% ± 4.3% in young adults ( P  = .002). HCL use was sustained at 12 months in adults (76.4% ± 2.2%, P  = .36) and older adults (80.4% ± 3.9%, P  = .36). HCL use of 70.6% was associated with 70% TIR (sensitivity 58.3%, specificity 85%, AUC 0.77). Older age, 80% or higher continuous glucose monitor use and four or more blood glucose checks per day were associated with attaining the HCL‐use threshold. Conclusions: HCL use of 70% or higher may be a useful target for clinicians to use to assist people with diabetes in attaining glycaemic goals. Youth may struggle with HCL use more than adults and require clinical intervention to help sustain HCL use across time.